Estimates of cancer burden in Tuscany. Issue 3 (May 2013) - Ventura, Leonardo; Miccinesi, Guido; Buzzoni, Carlotta; Crocetti, Emanuele; Paci, Eugenio; Foschi, Roberto; Rossi, Silvia
Aims and background: The Tuscan cancer registry has been operating since 1985, providing cancer incidence and survival data in Tuscany; it covers about 33% of the regional population. The purpose of this paper is to provide incidence, prevalence and mortality estimates for the major cancers in the whole Tuscany region for the period 1970—2015. Methods: The estimated figures were obtained by applying the MIAMOD method. Starting from mortality and survival data, incidence and prevalence were derived using a statistical back-calculation approach. Survival was modeled on the basis of published data from the Italian cancer registries. Results: According to the estimates, the most frequent cancer sites were colon-rectum in both genders, prostate in men and breast in women, with 4, 188, 3, 082 and 3, 092 new diagnoses, respectively, in 2012. The incidence rates were steadily increasing for lung cancer in women and melanoma in both sexes, while they were decreasing for uterine cervix cancer in women, lung cancer in men and stomach cancer in both sexes. For colorectal cancer a small reduction in incidence was estimated for both sexes in recent years. The incidence rates for prostate cancer, after a steep increase and subsequent stabilization, were estimated to increase slightly in the last years. The breast cancer incidence was estimated to stabilize in the last 10 years. The mortality trends were decreasing for all considered cancers except female lung cancer. Prevalence increased for most of the studied cancers except stomach cancer in both sexes, lung cancer in men and cervix cancer in women. The highest prevalence was estimated for breast cancer, with over 42, 000 cases in 2012. Conclusion: This paper provides an updated description of the cancer burden in Tuscany until 2015. These trends will have a significant impact on the regional health services and it is therefore important to enhance both primary prevention, for reducing the cancer incidence, and oncological surveillance, for evaluating the care and assistance of cancer patients.